2021
DOI: 10.1029/2021gl094687
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotactic Bacterial Activity in the North Pacific Ocean and Its Relationship to Asian Dust Inputs and Primary Productivity Since 8.0 Ma

Abstract: Magnetotactic bacteria (MTB) require iron and organic carbon for biomineralization, which can be supplied by dust inputs that stimulate primary productivity in iron-limited oceans. However, MTB activity and its relationship to Asian dust inputs and primary productivity are not well known in the North Pacific Ocean. Here, we present an eight-million-year record of magnetofossil abundance, Asian dust flux, and primary productivity from North Pacific sediments (Ocean Drilling Program Hole 885A). Our results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
2
14
1
Order By: Relevance
“…Magnetofossils in ideal magnetic SD sizes have been detected commonly in marine sediments during warm stages (Chang et al., 2012). The abundance of magnetofossils depends mainly on their production and preservation, which are sensitive to the paleoenvironment and can be affected by redox conditions, total organic carbon (TOC), deep‐water ventilation and oxygen solubility (Chang et al., 2018; Kopp et al., 2007; Roberts et al., 2011; Snowball et al., 2002; Suk, 2016; Zhang et al., 2021). The bottom oxygen concentration that is affected by changes in TOC and deep‐water ventilation could influence the preservation of magnetofossils (Mathias et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetofossils in ideal magnetic SD sizes have been detected commonly in marine sediments during warm stages (Chang et al., 2012). The abundance of magnetofossils depends mainly on their production and preservation, which are sensitive to the paleoenvironment and can be affected by redox conditions, total organic carbon (TOC), deep‐water ventilation and oxygen solubility (Chang et al., 2018; Kopp et al., 2007; Roberts et al., 2011; Snowball et al., 2002; Suk, 2016; Zhang et al., 2021). The bottom oxygen concentration that is affected by changes in TOC and deep‐water ventilation could influence the preservation of magnetofossils (Mathias et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, changes in the morphology distribution of magnetic mineral grain populations within natural samples can also be used to trace paleoenvironmental evolution. For example, it is suggested that the crystal shape of magnetofossils is indicative of total organic carbon flux (Hesse, 1994; Yamazaki, 2012; Yamazaki & Kawahata, 1998; Q. Zhang et al., 2021). Chang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that environmental factors apart from redox conditions, including iron supply (i.e., aeolian dust; Zhang et al, 2018Zhang et al, , 2021, organic carbon decomposition (e.g., Lu et al, 2021;Yamazaki & Kawahata, 1998), and temperature (Katzmann et al, 2013), potentially affect magnetofossil morphologies. Sites 1263 (∼1,500 m paleodepth) and 1262 (∼3,600 m paleodepth) show a similar pattern of iron concentration (Zachos et al, 2005), whereas reconstructed paleoredox conditions based on magnetofossils are different along the depth-transect (Figure 13), suggesting that iron supply likely had a negligible influence on the morphological features of magnetofossils on Walvis Ridge.…”
Section: Magnetofossil Reconstruction Of Paleodepth Gradient Redox Co...mentioning
confidence: 99%
“…Magnetofossil concentrations within deep-sea sediments may reflect a balance between their production and preservation, which relate to pore water chemistry, and ultimately the supply of organic carbon and dissolved oxygen (e.g., Larrasoaña et al, 2012;Roberts et al, 2011;Yamazaki & Horiuchi, 2016;Yamazaki & Ikehara, 2012;Zhang et al, 2018Zhang et al, , 2021. Sedimentary redox conditions may be affected by marine productivity (e.g., organic carbon delivery) and overlying seawater chemistry, and thus, the ocean's biogeochemical systems (Keeling et al, 2010;Oschlies et al, 2018).…”
mentioning
confidence: 99%